2009
DOI: 10.1016/j.jfoodeng.2009.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Water sorption and glass transition temperature of spray dried açai (Euterpe oleracea Mart.) juice

Abstract: a b s t r a c tSorption isotherms and glass transition temperature (T g ) of powdered açai juice were evaluated in this work. Powders were produced by spray drying using different materials as carrier agents: maltodextrin 10DE, maltodextrin 20DE, gum Arabic and tapioca starch. The sorption isotherms were determined by the gravimetric method, while the T g of powders conditioned at various water activities were determined by differential scanning calorimetry. As results, experimental data of water adsorption we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
124
0
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(166 citation statements)
references
References 39 publications
26
124
0
16
Order By: Relevance
“…The moisture contents of the spray-dried honey jackfruit powders were reduced from 7.30% (140°C) to 6.13% (180°C) when the inlet temperature was increased in this study (Table 3). The similar observation was obtained in different spray-dried fruit powders such as acai and watermelon (Tonon et al 2009;Quek et al 2007). This is due to rapid heat transfer between particles and drying air causing faster water removal (Solvol et al 2012).…”
Section: Spray Drying Effect Of Inlet Temperaturesupporting
confidence: 81%
See 1 more Smart Citation
“…The moisture contents of the spray-dried honey jackfruit powders were reduced from 7.30% (140°C) to 6.13% (180°C) when the inlet temperature was increased in this study (Table 3). The similar observation was obtained in different spray-dried fruit powders such as acai and watermelon (Tonon et al 2009;Quek et al 2007). This is due to rapid heat transfer between particles and drying air causing faster water removal (Solvol et al 2012).…”
Section: Spray Drying Effect Of Inlet Temperaturesupporting
confidence: 81%
“…Similar results were found by Nadeem et al (2011) whereby an increase of 21.7% and 36.0% was observed in product yield for mountain tea by increasing the carrier concentration from 0 to 3% and to 5% (w/w). However, Wong et al (2015) and Tonon et al (2009) reported that increasing the maltodextrin concentration decreased the powder yield of Sarawak pineapple and acai, respectively due to increasing of mixture viscosity. Moisture content and water activity of the spray-dried honey jackfruit powders decreased significantly (p \ 0.05) with the increase of maltodextrin concentration (Table 4).…”
Section: Effect Of Maltodextrin Concentrationmentioning
confidence: 97%
“…However, (Silva et al 2006) observed lower values of Tg for powder without carriers produced by freeze drying. By comparing the curves obtained for the compounds with those of (Tonon et al 2009). it is evident that the thermal decomposition of the powder changes with carrier concentration and type.…”
Section: Solubilitymentioning
confidence: 99%
“…Interestingly, the addition of gum Arabic impacted the hygroscopicity of samples in different ways: while it decreased the hygroscopicity of acerola pulp, less hygroscopic pomace samples were obtained when gum Arabic was added (p < 0.05, Table 1). In fact, acerola pulp is naturally highly hygroscopic due to the abundant presence of sugars and acids of low molecular weight that strongly interact with water molecules, mainly in the amorphous state (Figure 2, Jaya & Das, 2004;Tonon et al, 2009). For acerola pulp, the presence of gum Arabic affected the water interaction between molecules and a significant decrease of hygroscopicity in dried acerola pulp was observed (p < 0.05).…”
Section: Water Activity Hygroscopicity and Solubilitymentioning
confidence: 99%